1998
DOI: 10.1046/j.1365-2648.1998.00639.x
|View full text |Cite
|
Sign up to set email alerts
|

Predialysis patient education: effects on functioning and well‐being in uraemic patients

Abstract: This study evaluated the effects of a predialysis patient education programme on functioning and well-being in 28 uraemic patients. The programme consisted of four group sessions with the following themes: renal disease and dietary restriction, active renal replacement therapy, physical exercise, and the impact of chronic renal failure on economy, family and social life. Three to 9 months after having started dialysis the patients were evaluated regarding symptoms, perceived health (Health Index), functional (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
45
0
7

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(56 citation statements)
references
References 25 publications
4
45
0
7
Order By: Relevance
“…Alguns pesquisadores relatam que a ansiedade em paciente renal é frequente, pois a doença é percebida como ameaça à vida, à integridade corporal e como interrupção do meio de sobrevivência, prejudicando a identidade do paciente, sua autoridade e muitas vezes trazendo incertezas em relação ao seu futuro (Klang, Björvell, Berglund, Sundstedt & Clyne, 1998;Ramirez et al, 2012). As expressões de raiva dos pacientes são reações comuns à doença, como maneira de enfrentar a ansiedade e geralmente em resposta a uma ameaça, insulto ou lesões como punções e procedimentos dolorosos (Meireles, Goes & Dias, 2008).…”
Section: Discussionunclassified
“…Alguns pesquisadores relatam que a ansiedade em paciente renal é frequente, pois a doença é percebida como ameaça à vida, à integridade corporal e como interrupção do meio de sobrevivência, prejudicando a identidade do paciente, sua autoridade e muitas vezes trazendo incertezas em relação ao seu futuro (Klang, Björvell, Berglund, Sundstedt & Clyne, 1998;Ramirez et al, 2012). As expressões de raiva dos pacientes são reações comuns à doença, como maneira de enfrentar a ansiedade e geralmente em resposta a uma ameaça, insulto ou lesões como punções e procedimentos dolorosos (Meireles, Goes & Dias, 2008).…”
Section: Discussionunclassified
“…This study has found similar results with other studies, supporting the effectiveness of the training program in decreasing levels of stress. (Klang et al, 1998;Tsay &lee, 2005). However, in the study by Hiçdurmaz and Öz a statistically significant relationship was not encountered between the methods of coping with stress and the status of receiving training for hemodialysis in the hemodialysis patients (Hiçdurmaz & Öz, 2009).…”
Section: Discussionmentioning
confidence: 94%
“…The benefits of a multidisciplinary team approach to CKD care are well established, including delayed progression to ESRD and improved survival (1-3), improved patient psychologic profile (better moods and less anxiety), less physical functional disability (4,5), fewer HD catheter starts (2), and increased choice and likelihood of home-based dialysis modalities (2). However, we do not typically provide "excellent education to inform modality decision making."…”
Section: Discussion Of Question 1amentioning
confidence: 99%